Measurement of Ocular Compliance Using iPerfusion - Sherwood, Joseph M.; Boazak, Elizabeth M.; Feola, Andrew J.; Parker, Kim; Ethier, C. Ross; Overby, Darryl R. (Frontiers in Bioengineering and Biotechnology, 2019)
The pressure-volume relationship of the eye is determined by the biomechanical properties of the corneoscleral shell and is classically characterized by Friedenwald’s coefficient of ocular rigidity or, alternatively, by the ocular compliance (OC), defined as dV/dP. OC is important in any situation where the volume (V) or pressure (P) of the eye is perturbed, as occurs during several physiological and pathological processes. However, accurately measuring OC is challenging, particularly in rodents. We measured OC in 24 untreated enucleated eyes from 12 C57BL/6 mice using the iPerfusion system to apply controlled pressure steps, whilst measuring the time-varying flow rate into the eye. Pressure and flow data were analysed by a “Discrete Volume” (integrating the flow trace) and “Step Response” method (fitting an analytical solution to the pressure trace). OC evaluated at 13 mmHg was similar between the two methods (41 [37, 46] versus 42 [37, 48] nl/mmHg; mean [95% CI]), although the Step Response Method yielded tighter confidence bounds. OC was tightly correlated between contralateral eyes (R2=0.75, p=0.0003). Following treatment with the cross-linking agent genipin, OC decreased by 40 [33, 47]% (p=0.0001; N=6). This method to measure OC provides a powerful tool to assess corneoscleral biomechanics in mice and other species.